Pressure to change: a low-cost anatomically accurate cricoid pressure simulator for just-in-time training. (31st December 2018) - Parson, Mark; Duke, Nathaniel
Abstract : Cricoid pressure attempts to reduce the risk of aspiration during intubation. The technique is in routine use within the UK in line with current recommendations. Problems are often attributed to the application of an incorrect amount of force. Research has shown training to be limited in providing long-term benefit, with a skill retention period of <4 weeks. Using our previously created anatomically accurate comparatively low-cost cricoid pressure simulator, we have investigated the argument for cricoid pressure providers to perform just-in-time 'self-calibration' on a training device. The 'Crikey Trainer' device was used in four hospitals in South East England assessing 75 cricoid pressure providers. A structured interview examined: (1) cricoid pressure force before and after self-calibration; (2) associated skill knowledge; and (3) opinions on the device. 55% of participants successfully described cricoid ring location, 28% successfully described the force required. Difference between mean force and 30 Newton target improved in all groups after training (mean reduction 4.7N; p<0.0001). SD of measured force within each of the individual 30s tests reduced from an average of 3.0N (CI 2.62 to 3.36) to 2.09 (CI 1.75 to 2.42; p<0.0001). 97.3% of participants would consider using the device pre-Rapid Sequence Induction (RSI). We have developed an accurate cricoid pressure training device and improved cricoid pressure application force and variation. The data we and others have collected suggest that there is a place for regular pre-RSI self-calibration and that the majority of cricoid pressure providers would be receptive to it.